Irrevocable divorce, BaynunahSoghra, before Sharia courts inside the Green Line (An analytical study) - Zahra, Mohammed Saeed; Abu Wahdan, Abdullah Jamil (Journal of Islamic Sciences, 2024)
This research deals with the ruling on irrevocable divorce, a small Baynunah, starting with Sharia courts inside the Green Line, compared to the provisions of divorce in Islamic Sharia and according to other statutory laws. The reactionary divorce and the minor Baynunah divorce and the impact of each of them on the spouses and on the family bond. The spouses from the legal point of view, and the impact of irrevocable divorce by Baynounah Soghra in the Sharia courts inside the Green Line, and it was from this brief research that the Sharia courts within the Green Line - and in most cases - do not rule on revocable divorce; This results in stress on the husband in the event of divorce, as he will be bound by a new contract and dowry, even if he wants to take his wife back during the waiting period. In addition, in the case of a minor divorce, the spouses, according to the law in force within the Green Line, must share the property they acquired after marriage, after paying off their debts.